Food wastage in some public markets in Kinshasa City (Democratic Republic of the Congo) and consequences for the urban environment and public health - Armandine Mubwele; Blanchard Masasi Mayele; Emmanuel Makaly Biey; Camille Ipey Nsimanda; Koto-; Dieudonné Eyul'anki Musibono (Orapuh, Inc., 2024)
Introduction Food wastage is a significant global issue with adverse economic, social, environmental, and public health implications. Purpose This study aims to investigate the extent and impact of food wastage in various public markets within Kinshasa City. It seeks to understand the underlying causes and patterns of food wastage, the demographic characteristics of those involved, and the disposal methods employed. Additionally, the study explores the consequences of food wastage on the urban environment and public health. By providing a comprehensive analysis, this research intends to offer insights and recommendations for developing effective strategies to mitigate food wastage and its adverse effects on the city and its inhabitants. Methods The study utilized a combination of surveys, direct observations, and interviews to gather data on food wastage in Kinshasa. A sample of 100 individuals (representing 28.57% of the total market population) was randomly surveyed, and direct observations were made to assess the quantities of food wasted and the disposal methods used. Interviews were conducted to gather additional insights into practices and attitudes toward food wastage. The participants were characterized by low or medium education levels and were predominantly women and young single mothers. Results The study revealed that women constitute the majority of respondents in Kinshasa. Regarding food waste, the survey indicated that 40% of vegetables are wasted, followed by 30% of fruits, 20% of spices, and 10% of cereals. As for waste disposal, the survey revealed that none of the waste is directed to landfill sites as in other markets. Instead, 60% is thrown into the street, 30% into rivers, and a small percentage is either incinerated or used for composting. Conclusion Poor management of food waste increases health risks by attracting pests and causing environmental contamination, which can degrade water and soil quality. Addressing this issue requires implementing awareness campaigns to educate vendors and consumers about the impacts of food waste. Improving food handling practices, enhancing waste management infrastructure, supporting surplus food redistribution, and developing effective policies to reduce food waste are crucial actions to protect public health and promote a healthier urban environment in Kinshasa. These strategies are essential for ensuring food security and sustainability in the city, emphasizing the importance of sustainable consumption patterns and local product valorization through processing, preservation, and composting initiatives within a circular economy framework.